Inclusion and diversity within recruitment - Hunter, A; Lee, G (Bodleian Libraries, University of Oxford, 2022)
Within recruitment, it is always our aim to attract a diverse pool of candidates. This session will address the challenges we face and how we are working to overcome them, to ensure inclusion and diversity within our teams. We will focus on the importance of relevant, attractive advertising and the use of social media to enable maximum exposure. There will also be a chance to discuss in more detail any first-hand experiences and how we can strive to avoid the possibility of someone feeling excluded.